P-202 It's all about you . . . a person centred MDT development project. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Fradsham, Sarah; Bray, Dominic; Pryce, Ruth; Parfitt, Colette; Kirk, Emma; Carr, Clare; Howard, Lorraine; Howard, Anne
Abstract : Background: Our specialist palliative care unit is currently undertaking a project to improve the 'person-centredness' of the care it provides. It was recognised that the MDT (multidisciplinary team) meeting for our 26 inpatient beds could be improved both in terms of its productivity and its person-centredness. Aim: The aim of the project was to: Review our current inpatient MDT, recognising the strengths and weaknesses of it; Devise a new innovative model to be trialled and evaluated in the unit. Method: A multidisciplinary task and finish group was set up and the following aspects of the MDT meeting were considered: The team – membership, dynamics, contributions, culture; Infrastructure – environment and the role of technology; Meeting organisation; Person–centred decision making – is the patient's voice represented?; Governance – outcome measures. Prior to commencing the project a survey was carried out of all professionals attending the MDT to determine the effectiveness of the meeting in its current format, along with the value professionals felt was given to their contributions and role. MDT meetings in other organisations were also observed to help develop ideas for the new model. Results: The majority of staff surveyed felt the MDT could be improved significantly in its format and productiveness. A number of members of the MDT felt their role was not valued. Through the project a new model for working has been developed which is currently being trialled prior to evaluation. This model is thought to be a better representation of the patient voice along with acknowledging and reaffirming the value of all members of the MDT. Conclusions: The new MDT model is currently under evaluation. A research project has also been designed with the following aims: To investigate what are the patient–centred goals set at a weekly hospice inpatient MDT meeting? Are these goals being achieved?